2006
DOI: 10.1186/1471-2156-7-29
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium blocks, haplotype structure, and htSNPs of human CYP7A1 gene

Abstract: Background: Cholesterol 7-alpha-hydroxylase (CYP7A1) is the rate limiting enzyme for converting cholesterol into bile acids. Genetic variations in the CYP7A1 gene have been associated with metabolic disorders of cholesterol and bile acids, including hypercholesterolemia, hypertriglyceridemia, arteriosclerosis, and gallstone disease. Current genetic studies are focused mainly on analysis of a single nucleotide polymorphism (SNP) at A-278C in the promoter region of the CYP7A1 gene. Here we report a genetic appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Genetic variants of the CYP7A1 gene have been studied in human populations [70]. CYP7A1 genetic variants have been associated with defects in cholesterol and bile acid homeostasis [71].…”
Section: Specific Molecular Mechanisms Of Isoniazid/rifampicin-inducementioning
confidence: 99%
“…Genetic variants of the CYP7A1 gene have been studied in human populations [70]. CYP7A1 genetic variants have been associated with defects in cholesterol and bile acid homeostasis [71].…”
Section: Specific Molecular Mechanisms Of Isoniazid/rifampicin-inducementioning
confidence: 99%
“…Additionally, GLP-1 may improve insulin sensitivity in patients with type 2 diabetes and animal models [35]. CYP7A1 is the rate-limiting enzyme of the bile acid (BA) synthesis pathway, which is the pivotal mechanism for maintaining the balance between cholesterol and BA [36]. HMGCR is a key enzyme in the metabolism of glycolipids in the body and has been recognized as an important target for hypolipidemic drugs (statins).…”
Section: Discussionmentioning
confidence: 99%
“…The m204T>G is located in a region of conserved sequence containing several transcription factor binding motifs for PPARs and hepatocyte nuclear factor-4 (HNF4) [24] and represents the haplotype block covering a substantial part of the promoter and the first exon of this gene [25]. In vitro studies have indicated that PPARα and fibrate reduce the availability of HNF-4 for binding to the response sequence or competing with HNF-4 for the same binding site and therefore attenuate the transactivation of CYP7A1 by HNF-4 [24, 26].…”
Section: Discussionmentioning
confidence: 99%
“…However, the major allele of this variant displayed less responsiveness to fenofibrate-induce HDL–C increases compared with the minor allele. The differential modulation of these two variants on fenofibrate responses may stem from independent mechanisms which the two variants mediate as both variants are identified as tagging SNPs [25] with limited correlation and each representing an independent haplotype in a White population.…”
Section: Discussionmentioning
confidence: 99%